Experimental and numerical simulation of hollow structure under compression loading - Abdullah, Kassim Abdulrahman; Syed Mohamed Ali, Jaffar; Aminanda, Yulfian (Trans Tech Publications, Switzerland, 2012)
Buckling and crushing behaviour of hollow structure was studied through experiments and numerical simulation. The experimental material was a thin aluminium square tube (38 x 38, 1.2 mm thick). Quasi-static crushing load was applied using a Universal Testing Machine, Shimadzu Autograph (AG-X) series which uses TRAPEZIUMX software for control and data logging. Finite element simulation of the crushing test was done using LS-DYNA software. Results of the two analyses were compared and found in good agreement. The study provides an insight on ways to increasing energy absorption of light weight aluminium tubes. The simulation procedure can be used for further investigation of aluminium tubes of different cross section areas and geometries.